How to Read The Wealth of Nations (or Why the Division of Labor Is More Important Than Competition in Adam Smith). (June 2018) - Hearn, Jonathan
This article challenges the idea that competition was central to Adam Smith's thinking by scrutinizing the concept's role in Smith's work, particularly The Wealth of Nations . We will understand Smith's perspective better if we avoid reading later developments of the concept, particularly in economics, back into Smith's times and writings. Conversely, I argue that the division of labor is the governing idea providing the basic organizational structure of Wealth of Nations . Clarifying (and demoting) the role of competition in Smith's thinking requires showing the centrality of the idea of the division of labor—the idea doing the major analytic work in his thinking. The argument contributes to recent reassessments of the scope and significance of Smith's social theory and strengthens the view that his approach has more in common with historical and political sociology than with economics as currently configured.